دور تطبيق التكنولوجيا التدريسي وعلاج مشاكل تدريس اللغة العربية - Muhammad Zayinil Akhas (UIN Fatmawati Sukarno Bengkulu, 2020)
AbstractThe tremendous technology in the twentieth century and the beginning of the twenty-first century has a great impact on the progress and development of human life in all fields of life, the most important of which is the field of education, the many matters related to This field, whether in its objectives, methods, teaching methods or curricula. The researcher saw that this research is very important because it researches this topic and we saw it in four forms. The first is that the basic concepts should be taken care of as it is the basis for all learning procedures. The second is to understand the problems that the teacher has about learning procedures, and he must be known. Third, understanding the meaning of teaching technology and the purposes of its use in treating educational problems. Fourth, understanding the position of teaching technology in learning procedures. The researcher used a qualitative entrance. As for the type of research used, it is the descriptive and analytical method. And his procedures are that the researcher obtains the data sources, then analyzes the data, compares the data between the theoretical and the current one, and collects the data so that the analytical production gets to the existing educational problems. The researcher searched for analyzing the role of the application of instructional technology in treating the problems of teaching the Arabic language, as mentioned above. The result, as the researcher saw, is that the use of technology has an important role in the educational and learning fields.